The Melagiri Elephant Fence - A Crucial tool for Human-Elephant Control - Bilgi, Deepak S.; Kumar, S. R. Sanjeev (Indian Forester, 2021)
Effectively restraining elephants within forests and away from human use areas is critical to solving human-elephant conflict (HEC). Present methods such as solar fences, elephant proof trenches, alarm systems, scaring and driving methods have met with mixed results and not achieved the desired reduction in elephant crop depredation, human and elephant deaths. This case study showcases the successful development of the Melagiri Elephant Fence, using steel wire rope strands and precast steel reinforced concrete posts as the primary elements of the fence. The Melagiri Elephant Fence was field-tested in a high human-elephant conflict area of the Hosur Forest Division and monitored using camera traps. The final design of the fence was successful in containing even the most persistent and largest bull elephants. The Melagiri Elephant Fence is a cost-effective, permanent and maintenancefree elephant proof barrier for landscape-level occupancy planning and mitigation of human-elephant conflict. No injury to elephants, humans or other animals have been reported, and the fence may be considered as safe for use.